L'actualitat de la ciència política proposada per Francesc Eiximenis (ca. 1328/32-1409): el Regiment de la cosa pública i el Dotzè del Crestià al servei dels polítics (actuals). - MARTINES, VICENT (Scripta)
This article analyzes the contributions of medieval civic Humanism and the Renaissance to Political Science (with special attention to the theory of good government) and how current they can be effectively today. The analysis focuses on the contribution of Francesc Eiximenis with his Regiment de la cosa pública as part of his Dotzè del Crestià. We offer a brief anthology of excerpts (in their original version and translated into Spanish - in order to make it more accessible to a wider audience, especially, if possible, active politicians) with advice and teachings that can show how useful Francesc Eiximenis' conceptual proposal can be today.